The opportunities and challenges of social work interventions in disaster situations. (September 2015) - Dominelli, Lena
Professional social workers' positive contributions to humanitarian aid are seldom publicly acknowledged. If unaware of cultural sensitivities, locally defined needs and power relations, they are decried as oppressive. I use a research project to examine opportunities and challenges social workers have in developing empowering practices with victim–survivors of the 2004 tsunami in Sri Lanka. Whether reducing risks, mitigating disaster, providing relief or long-term reconstruction, social workers have much to offer. I suggest that the United Nations should include social workers more centrally within its humanitarian remit because social workers are professionally responsible for enhancing human well-being holistically.